Requirement Analysis and Solutions for Incoming and Outgoing Mail System for Local Water Company in Palembang, Indonesia - Marlindawati, .; Ratu Citra, Arsalina (INTI International University, 2023)
Requirements analysis (requirements engineering) is the process of determining user expectations for a new or modified product. It is usually a team effort and demands a variety of human soft skills, such as critical thinking, communication, and judgment. The research that we carried out is about email communication that needs to be established in a local water company namely PDAM Tirta Musi Palembang due to the lack of a fast, low-cost, accessible platform of communication in the company. Email communication or correspondence is essential because they are a reliable, valid, and authentic source of information This research aims to determine the requirement analysis and solutions in the form of procedures for managing incoming and outgoing mail at a local water company, namely PDAM Tirta Musi Palembang. The method that we used was descriptive observation and analysis, data collection techniques carried out by interviews, observation, and documentation review. Our study shows that the solutions to the current problem can be reduced by developing an incoming and outgoing email management system. Based on the user evaluation results, the perspective of usability and security of this system is necessary.